2018
DOI: 10.1039/c8cc05958f
|View full text |Cite
|
Sign up to set email alerts
|

Entwined dimer formation from self-complementary bis-acridiniums

Abstract: A dicationic tweezer incorporating two acridinium moieties linked by a 2,6-diphenylpyridine spacer was shown to self-assemble in an entwined dimer both in acetonitrile and water. The reaction was studied according to solvent polarity, temperature and concentration conditions. The entwined structure was confirmed in the solid state via single-crystal X-ray diffraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 34 publications
3
24
0
Order By: Relevance
“…All 1 H NMR spectrum signals of 2•2Cl (DMSO-d6, 298 K) were assigned using 2D NMR experiments (see ESI). Comparison of the 1 H NMR spectrum of 2•2Cl (c = 3 x 10 -3 mol L -1 ) to our previously reported bis-acridinium receptor 1•2Cl showed analogous chemical shifts for the acridinium protons ((H1/8) = 7.98 , (H 2/7 ) = 7.88, (H 3/6 ) = 8.45 and (H 4/5 ) = 8.90 ppm, see 13 This observation suggests that the acridinium protons of 2·2Cl are not affected by the electronic environment of the aromatic ring (phenyl or pyridyl) at their 9-position. Moreover, the spectrum of 2·2Cl did not show any signals related to the presence of its corresponding dimer as observed in 1•2Cl thus suggesting the dimer formation is less energetically favoured for (2)2·4Cl than for (1)2·4Cl.…”
supporting
confidence: 72%
See 4 more Smart Citations
“…All 1 H NMR spectrum signals of 2•2Cl (DMSO-d6, 298 K) were assigned using 2D NMR experiments (see ESI). Comparison of the 1 H NMR spectrum of 2•2Cl (c = 3 x 10 -3 mol L -1 ) to our previously reported bis-acridinium receptor 1•2Cl showed analogous chemical shifts for the acridinium protons ((H1/8) = 7.98 , (H 2/7 ) = 7.88, (H 3/6 ) = 8.45 and (H 4/5 ) = 8.90 ppm, see 13 This observation suggests that the acridinium protons of 2·2Cl are not affected by the electronic environment of the aromatic ring (phenyl or pyridyl) at their 9-position. Moreover, the spectrum of 2·2Cl did not show any signals related to the presence of its corresponding dimer as observed in 1•2Cl thus suggesting the dimer formation is less energetically favoured for (2)2·4Cl than for (1)2·4Cl.…”
supporting
confidence: 72%
“…In comparison to 1•2Cl, the relative positions of the nitrogen atoms in the spacer of 2•2Cl should not alter the optimum distance for - stacking interactions (7.1 Å) between both acridinium units. 14 In the present work, we report (i) the synthesis of a new bis-acridinium tweezer, (ii) the characterization of its self-association into an entwined dimer in water and (iii) the study of a 1:1 mixture of this new tweezer with our previously reported one (1•2Cl) 13 resulting in a narcissistic self-sorting process.…”
mentioning
confidence: 91%
See 3 more Smart Citations